Experience and trust: the benefits of mate familiarity are realized through sex-specific specialization of parental roles in Cassin’s auklet - Amy Yanagitsuru; Christopher Tyson; Frédéric Angelier; Michael Johns; Thomas Hahn; John Wingfield; Haley Land-Miller; Rebecca Forney; Elisha Hull (Royal Society Open Science, 2024)
Maintaining a pair bond year after year (perennial monogamy) often enhances reproductive success, but what familiar pairs are doing differently to improve success is unknown. We tested the hypothesis that endocrine changes mediate improvements in parental attendance in known-age Cassin’s auklets Ptychoramphus aleuticus, for which we found limited evidence. Instead, we found sex-specific parental roles in familiar pairs. Males modulated their nest attendance depending on the attendance of their mate, but the direction depended on mate familiarity. We suggest his flexibility may be mediated by prolactin. In a historical dataset, females with a familiar mate laid larger eggs that hatched into more robust chicks, but larger eggs correlated with lower female body condition. In study birds, attendance by males and females in good condition predicted chick weight, but attendance by females in poor condition did not, suggesting female-specific energetic constraint. Our findings suggest that males and females contribute differently to their joint reproductive fortunes, and that improvements in their respective roles may result in the benefits of mate familiarity. Since improved reproductive success is presumed to be a main benefit of maintaining a long-term pair bond, these results suggest a new avenue of research in the evolution of monogamy.